Identify Land Use and ITS Alignment Against RT/RW Pekalongan Regency - Hermanto Hermanto; Indarti Komala Dewi; Mujio Mujio (Jurnal Indonesia Sosial Teknologi, 2024)
Land use is the result of every form of intervention of human activities on land on the earth's surface that is dynamic and functions to meet the needs of life, both material and spiritual. Regional Spatial Planning is a form of intervention that is carried out so that human interaction with the environment can run harmoniously, harmoniously, and balanced. This aims to achieve human welfare. This study aims to identify land use in the Pekalongan Regency in 2023 and identify the alignment of land use with the RTRW of the Pekalongan Regency. The method used is the analysis of geographic information and the logical matrix of alignment. The results of the study show that the study area has 11 types of land use with the largest area, namely rice fields (3,223.34 Ha), settlements (2,611.46 Ha), and ponds (1,781.85 Ha). The alignment of land use with the RTRW obtained is divided into 3 (three), namely aligned, transitional, and not aligned with the area of 5,705.42 Ha, 605.86 Ha, and 2,821.58 Ha, respectively.